Disadaptive mental schemas according to family composition in Arequipa adolescents of public schools - Seperak Viera, Rosa Angélica (2019)
The impact of the family on the development of the individual has been the subject of much research, especially because of the structural variability in which it can be immersed. Moreover, it has gained prominence in the analysis of the psychological health of its members. The objective of this study was to perform an analysis of the maladaptive mental schemes according to the type of family structure in adolescents of 13 public schools in Metropolitan area of Arequipa. The Young Schema Questionnaire (YSQ-L2) was used as an instrument, which was validated in Perú by León and Sucari (2012). The results shows that there are differences between reconstructed homes and other structures in terms of the presence of maladaptive mental schemes of emotional deprivation, distrust, hypercritism and grandiosity.